PENGARUH KEBIJAKAN DIVIDEN DAN KEBIJAKAN HUTANG TERHADAP FINANCIAL DISTRESS PADA PERUSAHAAN MANUFAKTUR YANG TERDAFTAR DI BURSA EFEK INDONESIA PERIODE 2013-2022 - Setiowati, Rizky; Lisdawati (Journal of Research and Publication Innovation, 2024)
This research aims to test and obtain empirical evidence regarding the influence of dividend policy and debt policy on financial distress. This research uses a sample of manufacturing companies listed on the IDX in 2013-2022. The sampling method used in this research was purposive sampling, 24 companies were obtained as research samples. This type of research uses a quantitative approach. The data used in this research is secondary data originating from annual financial reports obtained via the BEI website, namely www.idx.co.id. The data analysis techniques used are descriptive statistical analysis, panel data regression model analysis, panel data regression model selection test, classical assumption test, panel data regression test and hypothesis testing using the e-views 12 program. The results of this study indicate that the dividend policy has not it could be said to have an effect on financial distress. This is proven by the probability value level of 0.2025<0.05. Debt policy influences financial distress. This is proven by the probability value level of 0.0000<0.05.